Diarrheagenic Escherichia coli pathotypes and childhood diarrhea in the Bikaner region of Western Rajasthan - Barupal, S.; Lakhani, J.; Harwani, D. (International Journal of Scientific Research in Biological Sciences, 2018)
Diarrhea caused by E. coli has been recognized as an important health problem among children in developing countries particularly in India and is a research priority of the diarrheal disease control program of the World Health Organization. Despite progress in preventing diarrhea and the spread of medical facilities in India, diarrhea remains the second leading cause of death in children, killing an estimated 321 children every day in 2015. It is the aim of the present research to gather information on current definitions, detection and prevalence, characterization of genetic determinants, virulence mechanisms, antibiotic resistance and epidemiology of the major DEC pathotypes with emphasis on the case studies conducted in the Bikaner region of Rajasthan in India. It has been found that the incidence of diarrheal diseases to be very high during the summer months followed by rainy or winter months in the Bikaner region of Rajasthan. Mode of water transportation, poor handling of water (at the household level), the presence of wastewater and unhygienic conditions predisposed children to diarrhea. In addition, indiscriminate stool disposal by mothers, lack of hand-washing before feeding their children or hand-washing without soap has also been observed to be associated with the increased threat of diarrheal infection. The health associated risks of diarrheagenic E. coli in under-five children and the possible solutions to prevent the same are discussed.